2005
DOI: 10.1128/jb.187.19.6862-6866.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mutator Phenotype Resulting from DNA Polymerase IV Overproduction in Escherichia coli : Preferential Mutagenesis on the Lagging Strand

Abstract: We investigated the mutator effect resulting from overproduction of Escherichia coli DNA polymerase IV. Using lac mutational targets in the two possible orientations on the chromosome, we observed preferential mutagenesis during lagging strand synthesis. The mutator activity likely results from extension of mismatches produced by polymerase III holoenzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 39 publications
4
74
0
Order By: Relevance
“…For example, the presence of a copy of the dinB gene on the FЈ episome in addition to the copy on the chromosome results in 4-fold more Pol IV and a 2-to 3-fold increase in mutation frequencies (22,36). The presence of the dinB gene on a multicopy plasmid results in 10-to 20-fold more Pol IV (36,73) and, depending on the mutational target, 5-to 200-fold increases in mutation frequencies (37,39,63,65,70,73,75). These observations strongly suggest that the mutagenic activity of Pol IV normally is tightly regulated in growing cells but that even a modest increase in abundance allows Pol IV to, at least partially, escape this regulation.…”
mentioning
confidence: 57%
“…For example, the presence of a copy of the dinB gene on the FЈ episome in addition to the copy on the chromosome results in 4-fold more Pol IV and a 2-to 3-fold increase in mutation frequencies (22,36). The presence of the dinB gene on a multicopy plasmid results in 10-to 20-fold more Pol IV (36,73) and, depending on the mutational target, 5-to 200-fold increases in mutation frequencies (37,39,63,65,70,73,75). These observations strongly suggest that the mutagenic activity of Pol IV normally is tightly regulated in growing cells but that even a modest increase in abundance allows Pol IV to, at least partially, escape this regulation.…”
mentioning
confidence: 57%
“…Recently, Kuban et al reported that dinB was found to make more errors on the lagging strand during synthesis than on the leading strand [36]. In our [G/C] 10 vector, the mononucleotide G repeat is located on the leading strand of synthesis.…”
Section: Pol IV and Microsatellite Mutagenesismentioning
confidence: 89%
“…Alternatively, the differential specificities could reflect a more complicated mode of mutation production in ⌬holE versus ⌬holE::hot strains. For example, accessory DNA polymerases, such as Pol II or Pol IV, have been shown to be involved in the production of mutations, particularly when Pol III has difficulty extending certain terminal mispairs (1,17). Possibly, HE without and HE containing Hot behave differently with respect to this phenomenon of polymerase trafficking.…”
Section: Discussionmentioning
confidence: 99%